Pengaruh pemberian air rebusan daun binahong (Anredera cordifolia) terhadap penyembuhan luka perineum pada ibu nifas - Muthia Sari Mardha; Endriani Syafitri; Desilisi Handayani (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Background: Data from the World Health Organization (WHO) records approximately 2.7 million cases of perineal wound pain in postpartum mothers. The projected figure is expected to reach 6.3 million by the year 2020. The issue of perineal wound pain is particularly significant in the Asian region, where around 50% of all cases occur. In Indonesia, about 75% of mothers who give birth via the vaginal route experience perineal wound pain. In this context, 57% of mothers experience pain in the area of the perineal wound, with 28% undergoing episiotomies and 29% experiencing spontaneous perineal tears. The purpose of this study was to find out whether there is an impact of decoction of binahong plants on the recovery of tears in the birth canal in postpartum mothers.Methods: Variations in this study are quasi-experimental or quasi-experimental with the Post-test Only Control Group research design.Data were obtained by distributing questionnaires, while data analysis used the Paired Sample T Test The sample in this study was 22 respondents.Results: The statistical test results indicate the influence of administering boiled binahong leaf infusion (Anredera cordifolia) on the healing of perineal wounds in postpartum mothers at Lena Barus Clinic, East Binjai Subdistrict, with a p-value of 0.000. Conclusion: This study concludes that there is an impact of administering boiled binahong leaf infusion on the healing of perineal wounds in postpartum mothers. It is hoped that healthcare facilities can consider the provision of boiled binahong leaf infusion as part of complementary therapy to aid in the recovery process of perineal tears in postpartum mothers.